Investigation of the effect of various silicon contents on the crystallization pattern and the composition of silumin phases. (July 2020) - Cherepanov, A I; Kukartsev, V A; Tynchenko, V S; Korpacheva, L N; Makarchuk, I Yu; Dremin, R S
Abstract: Silumin is an alloy composed of aluminum and silicon, that can contain up to 22% of silicon. It has a low cost, wear resistance and low relative weight. The main industries for using silumin are aircraft manufacturing and mechanical engineering. Given the relatively low cost of the alloy, silumin is used to produce cheap household appliances, which are often not inferior in reliability to expensive analogues. Recently, silumin has gained particular popularity in the arms industry, especially for the production of air rifles. The properties of these alloys primarily depend on the Si content, which leads to changes in its microstructure. The paper presents studies of the effect of silicon content on changes in the nature of crystallization and phase composition of silumins with Si content from 1 to 21%.